Chekhov in the Times of Lockdown: Gary Shteyngart’s Our Country Friends as a “Fable of Our Broken Time”. - Bryla, Martyna Marika (My University, 2023)
Inspired by the theme of the 2023 PAAS Conference, this paper approaches Our Country Friends (2021) by Russian-American author Gary Shteyngart as a novel which is at once atemporal and painfully contemporary.
Keywords: Novela estadounidense; Literatura contemporánea; Gary Shteyngart - Crítica e interpretación; Gary Shteyngart; Anton Chekhov; COVID-19; Donald Trump; Time